Reduced graphene oxide modified electrodes for sensitive sensing of gliadin in food samples - Chekin, Fereshteh; Singh, Santosh K.; Vasilescu, Alina; Dhavale, Vishal M.; Kurungot, Sreekumar; Boukherroub, Rabah; Szunerits, Sabine (ACS Sensors, 2016)
Incidences of food allergies are on the rise, which can greatly affect the well-being of children as well as adults. Intolerance to gluten, a protein composite of gliadin and glutenin, present in wheat, barley, and rye and several cereals, can be the causative agent of celiac disease (CD) and other allergic reactions. A gluten-free diet has become essential for people affected by CD, and consequently, the amount of gluten in food products needs to be strictly controlled. In this paper, we report an electrochemical label-free immunosensor for ultrasensitive and specific detection of gliadin. The sensor takes advantage of the specific properties of porous reduced graphene oxide (prGO) covalently functionalized with anti-gliadin antibodies using 1-pyrenecarboxylic acid as linker molecule. Using differential pulse voltammetry (DPV) and [Fe(CN)6](3-/4-) as a redox probe, a decrease of current is linked to the presence of gliadin. The sensor achieved a detection limit of 1.2 ng mL(-1) over a 1.2-34 ng mL(-1) linear range with high selectivity. The advantages offered by this sensor are the possibility to regenerate the surface of the immunosensor, its rapid and ease of production, as well as applicability for the screening of gliadin concentrations in real food samples, as shown here.
Keywords: anti-gliadin antibody; food samples; gliadin; Immunosensor; Porous reduced graphene oxide

On demand electrochemical release of drugs from porous reduced graphene oxide modified flexible electrodes - Boulahneche, Samia; Jijie, Roxana; Barras, Alexandre; Chekin, Fereshteh; Singh, Santosh K.; Bouckaert, Julie; Medjram, Mohamed Salah; Kurungot, Sreekumar; Boukherroub, Rabah; Szunerits, Sabine (Journal of Materials Chemistry B, 2017)
Despite the advantages of an electrochemical control for drug release, only a handful of electrochemical-based release systems have been developed so far. We report herein on the development of an electrochemically activatable platform for on-demand delivery of drugs. It is based on flexible gold thin film electrodes coated with porous reduced graphene oxide (prGO) nanosheets onto which the drug of interest has been integrated beforehand. Two different drugs are investigated here: ondansetron hydrochloride (ODS), a selective 5-HT3 receptor antagonist used for preventing nausea and vomiting caused by chemotherapy and radiotherapy, and ampicillin (AMP), an antibiotic to prevent and treat a number of bacterial infections such as respiratory tract infections, urinary tract infections, and meningitis. In the case of ODS, application of a negative potential bias of -0.8 V results in a sustained slow ODS release with an ODS flux of 47 mu g cm(-2) h(-1). In the case of AMP, we show that polyethyleneimine modified prGO (prGO/PEI) is an extremely efficient matrix. Upon the application of +0.8 V, 24% of AMP could be released from the electrical interface in a time span of 2 h. The released AMP kept its antibacterial activity as demonstrated by antimicrobial tests. These examples illustrate the major benefits of the developed approach for biomedical applications.

Porous reduced graphene oxide modified electrodes for the analysis of protein aggregation. part 1: lysozyme aggregation at pH 2 and 7.4 - Vasilescu, Alina; Boulahneche, Samia; Chekin, Fereshteh; Gaspar, Szilveszter; Medjram, Mohamed Salah; Diagne, Abdou Aziz; Singh, Santosh K.; Kurungot, Sreekumar; Boukherroub, Rabah; Szunerits, Sabine (Electrochimica Acta, 2017)
Protein instability due to misfolding and aggregation is of big concern for protein based therapeutics because it impacts the bioavailability and immunogenicity of such drugs. The development of simple and cost-effective methods for the analysis of pharmaceutical formulations, indicating the presence or absence of protein aggregates, is consequently of high importance. This work proposes a novel electrochemical interface based on porous reduced graphene oxide coated glassy carbon electrode (GC/prGO) allowing for the early and sensitive identification of protein aggregation by following the change in the oxidative current of the proteins. The novelty of this work lies in the exploration of the ability of GC/prGO interfaces to capture different aggregation behaviors. Lysozyme is used as a model to follow by electrochemistry its aggregation at two pH values, pH 2 and pH 7.4, leading to the formation of amyloid and amorphous aggregates, respectively. Comparing the oxidation peak of lysozyme by differential pulse voltammetry (DPV) for different electrode architectures allowed validating the higher sensitivity of the GC/prGO interface versus bare glassy electrodes or electrodes coated with non-porous reduced graphene oxide. Parallel experiments were performed by fluorescence with thioflavin T, size exclusion chromatography and Atomic Force Microscopy (AFM) imaging. These tests further highlighted the usefulness of GC/prGO electrode to visualize in a fast and reliable manner the changes in the protein structure and the differences between the processes occurring at pH 2 and pH 7.4. In particular, the ability to emphasize changes related to the first steps in aggregation that could be indicative of the aggregation course, recommend the GC/prGO electrode in combination with DPV as a new analytical tool for aggregation studies of biopharmaceuticals. Part 2 of this work will demonstrate later the utility of this approach for the analysis of a fast acting injectable human insulin formulation, Humulin R, used for diabetes treatment as well as for calcitonin. (C) 2017 Elsevier Ltd. All rights reserved.

Nucleic aptamer modified porous reduced graphene oxide/MoS2 based electrodes for viral detection: application to human papillomavirus (HPV) - Chekin, Fereshteh; Bagga, Komal; Subramanian, Palaniappan; Jijie, Roxana; Singh, Santosh K.; Kurungot, Sreekumar; Boukherroub, Rabah; Szunerits, Sabine (Sensors and Actuators B-Chemical, 2018)
Next to graphene nanomaterials, molybdenum disulfide (MoS2) offers large surface area that can enhance its biosensing performance. In this work, we investigate the performance of glassy carbon (GC) electrodes modified successively with porous reduced graphene oxide (prGO) and molybdenum sulfide (MoS2) for the sensitive and selective detection of the L1-major capsid protein of human papilloma virus (HPV). Owing to the difficulties to perform serological assays and HPV culture efficiently, tools based on molecular recognition are becoming of great importance. We developed here an electrochemical sensor for HPV upon covalent functionalization of the electrode with an aptamer Sc5-c3, a RNA aptamer targeted against the HPV-16 L1 protein. Using differential pulse voltammetry (DPV) and an optimized sensor interface, a linear relationship between the peak current density of a redox couple such as [Fe(CN)6]4- and the concentration of HPV-16 L1 proteins in the range of 0.2-2 ng mL(-1) (3.5 pM-35.3 pM) could be reached with a detection limit of 0.1 ng mL(-1) (1.75 pM). Cross-reactivity studies demonstrated high selectivity over potential interfering species such as HPV-16 E6, opening new opportunities of the developed concept for the development of point of care devices. (C) 2018 Elsevier B.V. All rights reserved.

Sensitive electrochemical detection of cardiac troponin I in serum and saliva by nitrogen-doped porous reduced graphene oxide electrode - Chekin, Fereshteh; Vasilescu, Alina; Jijie, Roxana; Singh, Santosh K.; Kurungot, Sreekumar; Iancu, Madalina; Badea, Gabriela; Boukherroub, Rabah; Szunerits, Sabine (Sensors and Actuators B-Chemical, 2018)
Cardiovascular diseases pose one of the highest mortality risks among all diseases in developed countries, steadily increasing the burden on the health systems. Early diagnosis of cardiovascular diseases has consequently become highly important to decrease mortality and to use more adapted therapeutic decisions. We demonstrate here the utility of nitrogen-doped reduced graphene oxide (N-prGO) for detecting and quantifying of cardiac troponin I (cTnI), a key human cardiac protein biomarker, under physiologically relevant conditions. Non-covalent modification of N-prGO by 1-pyrenecarboxylic acid (py-COOH) and poly(ethylene glycol) modified pyrene (py-PEG) ligands allowed the covalent integration of Tro4 aptamer, known for its high selectivity towards cTnI. Using differential pulse voltammetry (DPV), a label-free electrochemical sensor for cTnI for concentrations down to 1 pgmL(-1) in human serum could be obtained. This sensitive detection arises from the integration of a porous nanomaterial with excellent electrochemical properties being easily amendable to site-specific surface modification. (C) 2018 Elsevier B.V. All rights reserved.

Graphene-modified electrodes for sensing doxorubicin hydrochloride in human plasma - Chekin, Fereshteh; Myshin, Vladyslav; Ye, Ran; Melinte, Sorin; Singh, Santosh K.; Kurungot, Sreekumar; Boukherroub, Rabah; Szunerits, Sabine (Analytical and Bioanalytical Chemistry, 2019)
Doxorubicin (DOX), an anthracycline molecule, is currently one of the most widely used anticancer drugs in clinics. Systematic treatment of patients with DOX is known to be accompanied by several unpleasant side effects due to the toxicity of the drug. Thus, monitoring of DOX concentration in serum samples has become increasingly important to avoid side effects and ensure therapeutic efficiency. In this study, we discuss the construction of a disposable electrochemical sensor for the direct monitoring of DOX in clinical blood samples. The sensor is based on coating a gold electrode in a flexible integrated electrode construct formed on polyimide sheets using photolithography, with nitrogen-doped reduced graphene oxide (N-rGO) suspended in chitosan. Under optimized conditions, a linear relationship between the oxidative peak current and the concentration of DOX in the range of 0.010-15M with a detection limit of 10nM could be achieved. The sensor was adapted to monitor DOX in serum samples of patients under anticancer treatment.
Keywords: Disposable electrodes; doxorubicin; Nitrogen-doped reduced graphene oxide; Serum